Early warning epidemic surveillance in the Pacific island nations: an evaluation of the Pacific syndromic surveillance system. Issue 7 (18th May 2016) - Craig, Adam T.; Kama, Mike; Samo, Marcus; Vaai, Saine; Matanaicake, Jane; Joshua, Cynthia; Kolbe, Anthony; Durrheim, David N.; Paterson, Beverley J.; Biaukula, Viema; Nilles, Eric J.
Abstract: Objective: The Pacific Syndromic Surveillance System (PSSS), launched in 2010, provides a simple mechanism by which 121 sentinel surveillance sites in 21 Pacific island countries and areas perform routine indicator‐ and event‐based surveillance for the early detection of infectious disease outbreaks. This evaluation aims to assess whether the PSSS is meeting its objectives, what progress has been made since a formative evaluation of the system was conducted in 2011, and provides recommendations to enhance the PSSS's performance in the future. Methods: Twenty‐one informant interviews were conducted with national operators of the system and regional public health agencies that use information generated by it. Historic PSSS data were analysed to assess timeliness and completeness of reporting. Results: The system is simple, acceptable and useful for public health decision‐makers. The PSSS has greatly enhanced Pacific island countries' ability to undertake early warning surveillance and has contributed to efforts to meet national surveillance‐related International Health Regulation (2005) capacity development obligations. Despite this, issues with timeliness and completeness of reporting, data quality and system stability persist. Conclusion: A balance between maintaining the system's simplicity and technical advances will need to be found to ensure its long‐term sustainability, given the low‐resource context for which it is designed.